Genetic consequences of breaking migratory traditions in barnacle geese Branta leucopsis. Issue 23 (7th November 2013) - Jonker, R. M.; Kraus, R. H. S.; Zhang, Q.; van, P.; Larsson, K.; van der, H. P.; Kurvers, R. H. J. M.; van, S. E.; Loonen, M. J. J. E.; Crooijmans, R. P. M. A.; Ydenberg, R. C.; Groenen, M. A. M.; et al.
Abstract Cultural transmission of migratory traditions enables species to deal with their environment based on experiences from earlier generations. Also, it allows a more adequate and rapid response to rapidly changing environments. When individuals break with their migratory traditions, new population structures can emerge that may affect gene flow. Recently, the migratory traditions of the Barnacle Goose Branta leucopsis changed, and new populations differing in migratory distance emerged. Here, we investigate the population genetic structure of the Barnacle Goose to evaluate the consequences of altered migratory traditions. We used a set of 358 single nucleotide polymorphism (SNP) markers to genotype 418 individuals from breeding populations in Greenland, Spitsbergen, Russia, Sweden and the Netherlands, the latter two being newly emerged populations. We used discriminant analysis of principal components, FST, linkage disequilibrium and a comparison of geneflow models using migrate‐n to show that there is significant population structure, but that relatively many pairs of SNPs are in linkage disequilibrium, suggesting recent admixture between these populations. Despite the assumed traditions of migration within populations, we also show that genetic exchange occurs between all populations. The newly established nonmigratory population in the Netherlands is characterized by high emigration into other populations, which suggests more exploratory behaviour, possibly as a result of shortened parental care. These results suggest that migratory traditions in populations are subject to change in geese and that such changes have population genetic consequences. We argue that the emergence of nonmigration probably resulted from developmental plasticity.